Performance and carcass characteristics of broilers fed diets supplemented with organic chromium, mannan oligosacchaarides, and zinc bacitracin - Mateo, Carmelita D.; Billena, Mylen S.; Carandang, Nelia F. (2000)
Five hundred male day-old Arbor Acre broiler chicks were used in a 42-day feeding trial to determine the effects of organic chromium (Cr) from yeast, mannan oligosaccharides (MOS) and zinc bacitracin (ZnB) supplementation on performance and carcass characteristics of broilers.

Performance of birds fed with diets supplemented with a growth promotant was better than that of birds fed without it. Supplementation of broiler feed with Cr and MOS in combination with ZnB, and MOS alone, significantly increased live body weight, weight gain, and feed efficiency during the first 3 weeks of life. MOS alone or in combination with ZnB proved to be superior to ZnB alone in improving growth performance of broilers, showing that MOS can replace the feed antibiotic, ZnB, to improve performance and carcass characteristics of broilers during the first 3 weeks of life. The combination of Cr and ZnB also positively influenced growth performance of broilers. The effects of MOS and Cr supplementation were not significant during the grower period.
Keywords: Broiler chickens -- Feeding and feeds; Animal feeds; Feed additives